Clarifying the interplate main tectonic elements of Western Anatolia, Turkey by using GNSS velocities and Bouguer gravity anomalies. (15th October 2017) - Çırmık, Ayça; Pamukçu, Oya
Graphical abstract: Highlights: GNSS velocities are towards S-SW with respect to the Anatolian block fixed frame. Three tectonic regions are figured out due to the Anatolian block solutions. GNSS velocities are towards N with respect to the Aegean block fixed frame. The N-S trending structure is obtained along 28°longitude by filtered gravity data. Abstract: In this study, the GNSS and gravity data were processed and compared together for examining the continental structures of the Western Anatolia region which has very complicated tectonism. The GNSS data of three national projects were processed and GNSS velocities were found as approximately 25 mm per year towards southwest with respect to the Eurasia fixed frame. In order to investigate the interplate motions of the region, the Anatolian and Aegean block solutions were calculated and the differences in directions and amplitudes of velocities were observed particularly in the Anatolian block solution. Due to the Anatolian block solutions, the study area was grouped into three regions and compared with the tectonic structures as the first time for Western Anatolia by this study. Additionally, W-E and N-S relative GNSS solutions were obtained for observing the possible tectonic borders of the study area. Besides, 2nd order horizontal derivative and low-pass filter methods were applied to Bouguer gravity anomalies and the results of the gravity applications and the changes on crustal-mantle interface were compared with the GNSS horizontal velocities.